2010
DOI: 10.1007/s00247-009-1531-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography in patients with cystic fibrosis

Abstract: Considering the limitations of US and the low risk-benefit rate of liver biopsy in most CF patients, this preliminary study suggests that TE is an attractive non-invasive way to assess and follow-up liver disease in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 34 publications
6
74
0
Order By: Relevance
“…Pathognomonic hepatic manifestations of cystic fibrosis (CF) is biliary cirrhosis which leads to CF-associated liver disease (CFLD) in around one-quarter of patients [21]. Conventional ultrasound examination with B-mode seems to be insufficient in assessing liver condition in patients with CF [22].…”
Section: Cf-associated Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Pathognomonic hepatic manifestations of cystic fibrosis (CF) is biliary cirrhosis which leads to CF-associated liver disease (CFLD) in around one-quarter of patients [21]. Conventional ultrasound examination with B-mode seems to be insufficient in assessing liver condition in patients with CF [22].…”
Section: Cf-associated Liver Diseasementioning
confidence: 99%
“…Research conducted by Behrens et al and Menten et al compares respectively ARFI and TE value to B-mode. In spite of its good results, its value is slightly decreased due to this limitation [21,23]. Friedrich-Rust et al used ARFI, TE and biochemical markers of fibrosis on 106 adult patients with fibrosis.…”
Section: Cf-associated Liver Diseasementioning
confidence: 99%
“…Especially in adult patients with chronic hepatic diseases, a strong association of liver stiffness measured by FS and the histologically determined degree of liver fibrosis was shown [9][10][11]. Recently, this method was shown to provide valid results in pediatric patients with liver diseases, such as viral hepatitis, Wilson disease, alpha-1-antitrypsin deficiency, and cystic fibrosis [12,13]. We analyzed the detection of liver fibrosis using FS compared with conventional ultrasound in pediatric patients with cystic renal diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, another study found that elasticity values of controls, pancreatic sufficient CF patients and pancreatic insufficient CF patients with an ultrasound showing either normal or homogenously hyperechoic livers, were comparable and significantly lower than in CF patients with heterogenous, nodular livers or with evidence of portal hypertension on ultrasound (P <0.002). Interestingly, it was found that male adults and male children with CF had significantly higher liver stiffness than females in the same group (P=0.0013) (31).…”
Section: Cystic Fibrosismentioning
confidence: 99%